Transnational environmental agreements with heterogeneous actors - Achim Hagen; Leonhard Kähler; Klaus Eisenack (University of Oldenburg, Department of Economics, 2016)
This paper explores transnational environmental agreements on climate change. As the Paris agreement of 2015 contains no binding emission reduction targets for nation states, understanding other forms of cooperation as complements to the United Nations Framework Convention on Climate Change (UNFCCC) process becomes increasingly important. We thus aim to identify directions for further research on agreements with heterogeneous contracting parties. By building on empirical examples of emerging transnational environmental agreements, and on insights from the global governance literature, we discuss the scope and limits of the current economic literature on international environmental agreements. We argue that further game theoretical research would benefit from extending the analysis (i) to consider actors that are not nation state governments, and (ii) to consider multiple environmental agreements that are in force at the same time. We underpin this claim by suggesting two proposals for economic models that analyze climate clubs and city alliances. The results show that transnational environmental agreements can be individually rational and can improve the effectiveness of climate policies.
Keywords: C72; Q54; 330; heterogeneous actors; international environmental agreements; transnational agreements